Constitutivism, Error, and Moral Responsibility in Bishop Butler's Ethics. Issue 4 (1st December 2017) - Dick, David G.
Abstract: In his writings on moral philosophy, Bishop Joseph Butler adopts an identifiably "constitutivist" strategy because he seeks to ground normativity in features of agency. Butler's constitutivist strategy deserves our attention both because he is an influential precursor to much modern moral philosophy and because it sheds light on current debates about constitutivism. For example, Butler's approach can easily satisfy the "error constraint" that is often thought to derail modern constitutivist approaches. It does this by defining actions relative to the kind of being who performs them, instead of relative to the circumstances of their performance. This gives Butler a conceptually stable account of something that is both fully an action yet morally bad, for which an agent might be held morally responsible. Should modern constitutivists wish to model their views on Butler's in order to satisfy the error constraint, they need not adopt all his theological and other commitments, but they will have to avoid the currently popular constitutivist strategy of deriving normative force from the inescapability of a given principle.